2006
DOI: 10.1074/jbc.m508933200
|View full text |Cite
|
Sign up to set email alerts
|

TEDS Site Phosphorylation of the Yeast Myosins I Is Required for Ligand-induced but Not for Constitutive Endocytosis of the G Protein-coupled Receptor Ste2p

Abstract: The yeast myosins I Myo3p and Myo5p have well established functions in the polarization of the actin cytoskeleton and in the endocytic uptake of the G protein-coupled receptor Ste2p. A number of results suggest that phosphorylation of the conserved TEDS serine of the myosin I motor head by the Cdc42p activated p21-activated kinases Ste20p and Cla4p is required for the organization of the actin cytoskeleton. However, the role of this signaling cascade in the endocytic uptake has not been investigated. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…To date, Ypk2 substrates or downstream effectors involved in regulating actin organization and/or cell wall integrity have remained elusive. One interesting candidate is a yeast type I myosin protein Myo5, which can be phosphorylated by Ypk2 in vitro (42) and has been implicated in regulating the actin assembly (43). Further investigation is required to see whether Ypk2 334 -677 can phosphorylate Myo5 or to uncover other Ypk2 downstream effectors and examine their interactions with Ypk2 334 -677 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, Ypk2 substrates or downstream effectors involved in regulating actin organization and/or cell wall integrity have remained elusive. One interesting candidate is a yeast type I myosin protein Myo5, which can be phosphorylated by Ypk2 in vitro (42) and has been implicated in regulating the actin assembly (43). Further investigation is required to see whether Ypk2 334 -677 can phosphorylate Myo5 or to uncover other Ypk2 downstream effectors and examine their interactions with Ypk2 334 -677 .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the TEDS site is essential for ligandinduced Ste2 internalization [38]. However, Cdc42 and the PAKs are dispensable, suggesting that other signalling cascades can control TEDS site phosphorylation [38]. Consistently, it was demonstrated that the yeast SGK (serum and glucocorticoid-induced kinase) homologue Ypk2 interacts with Myo5 and can phosphorylate its TEDS site [38].…”
Section: Regulation Of the Recruitment And The Biochemical Activitiesmentioning
confidence: 90%
“…However, even though the TEDS site phosphorylation is required for endocytic uptake [6,38], the role of the Cdc42/PAK signalling cascade in endocytosis is far from being understood. Phosphorylation of the TEDS site is essential for ligandinduced Ste2 internalization [38]. However, Cdc42 and the PAKs are dispensable, suggesting that other signalling cascades can control TEDS site phosphorylation [38].…”
Section: Regulation Of the Recruitment And The Biochemical Activitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Phosphorylation at this site, also known as the TEDS rule site [Bement and Mooseker, 1995] is required to activate ATPase activity and functional motility in ameboid class I myosin [Wu et al, 1997;Novak and Titus, 1998;Yamashita and May, 1998;Grosshans et al, 2006]. We theorized that phosphorylation at the equivalent site in myosin VI, threonine 406 (T406), could serve as the motor-to-tether signal.…”
Section: Introductionmentioning
confidence: 98%